Peningkatan efisiensi lintasan produksi dengan metode line balancing Kilbridge & Wester - Nazareth, Juan Rafael; Dewi, Ratna Mustika (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
In the manufacturing industry, production line efficiency is an important factor to maximize output and reduce delays. One of the methods used to achieve this goal is line balancing. This research aims to maximize output and reduce balance delay using the Killbridge and Wester line balancing method. The Killbridge and Wester method is used to analyze and balance the production line by combining several operations into one work station, so that the operating time at each station is reduced and more balanced. The results showed a significant increase in production line efficiency. As a result of the author's line balancing, the line efficiency increased from 65.76% to 84.55%, and the smoothest index decreased from 7.33 to 2.77. The author succeeded in combining several operations into one workstation that was more balanced in terms of operating time. The line balancing analysis process that has been analysis process that has been carried out shows an increase in output and a reduction in production time, however still requires further testing to calculate the optimum number of operators at each workstation. in each work station. The line balancing that was carried out proved to be effective in improving production efficiency.